Implementation Fernando Martinez’s Practice Methods On Drumset Instrument Class Alfiah Akbar - Mohamad Alfiah Akbar (Institut Seni Indonesia Yogyakarta, 2020)
This study aims to (1) Know the improvement in student learning outcomes in the drumset instrument class after applying the Fernando Martinez practice method; and (2) Knowing the obstacles that exist during the application of the Fernando Martinez (FM) practice method. The research method used is classroom action research (CAR) carried out in two cycles. The stages in this study include the planning, action, observation, and reflection stages. Data obtained include student learning outcomes, observations of student drumset practice activities obtained from videos and observation sheets, as well as the results of interviews. The results of the study in the first cycle showed that there was an increase in student learning outcomes, but the learning outcomes had not yet reached the indicators of learning achievement, namely the minimum score with a very good category (90-100). While the results of the research in the second cycle there is an increase in student learning outcomes that are significant when compared with before the application of the FM practice method and in first cycle. The obstacles faced when conducting research in the first and second cycles include; lack of motivation of students towards the tasks given, students have not been able to master the material well, because the FM method is new so students are not familiar. the stages of the FM practice method in first cycle have not been carried out correctly, the collection of tasks in the first cycle in this case the practice video was not collected on time.